Embarkation: Reimagining a Taoist Ritual Ceremony - Shin Yu Pai (Genealogy, 2020)
Poet and artist Shin Yu Pai shares the origins and process of creating her performance video piece Embarkation. Informed by Buddhist and Taoist rituals from Bhutan and Taiwan, Pai reflects on her efforts to reimagine a traditional Taoist ceremony in the context of a personal grief ritual performed for the stage. She discusses the process of collaborating with film, video, theater, and movement artists from both Taiwan and Seattle, including Ye Mimi, Scott Keva James, Jane Kaplan and Vanessa DeWolf, and how her vision evolved over many iterations. The roles of community, audience, and creative friendships are also explored in the context of how they can invigorate a creative work.